2018
DOI: 10.1371/journal.pone.0207480
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and insights into recombination signals in lumpy skin disease virus recovered in the field

Abstract: Wide spread incidences of vaccine-like strains of lumpy skin disease virus (LSDV) have recently been reported in a Russian region with a neighboring country that actively vaccinate with a live attenuated LSD vaccine. The use of live-attenuated viruses (LAVs) as vaccines during an active outbreak, creates potential ground for coinfection of hosts and emergence of a strain combining genetic fragments of both parental vaccine and field strains. In this study, we analyse the vaccine-like strain LSDV RUSSIA/Saratov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
145
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(168 citation statements)
references
References 35 publications
2
145
1
Order By: Relevance
“…It was earlier reported that attempts to experimentally reproduce fulminating LSDV disease presentation could fail (Irons et al.,; Osuagwuh, Bagla, Venter, Annandale, & Irons, ). Moreover, when more full‐genome sequences of recent, archived, and other genetic variants of LSDV strains become available (Sprygin, Babin, et al., ), a deeper understanding should be obtained to clarify the possible links between viral genetic signatures and disease presentation.…”
Section: Discussionmentioning
confidence: 99%
“…It was earlier reported that attempts to experimentally reproduce fulminating LSDV disease presentation could fail (Irons et al.,; Osuagwuh, Bagla, Venter, Annandale, & Irons, ). Moreover, when more full‐genome sequences of recent, archived, and other genetic variants of LSDV strains become available (Sprygin, Babin, et al., ), a deeper understanding should be obtained to clarify the possible links between viral genetic signatures and disease presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Alexander et al (2019) reported the development of a new real-time PCR for the detection of LSD virus (LSDV) field, vaccine and recombinant strains as a follow-up of the finding byKononov et al (2019) of vaccine-like LSDV strains outbreaks in Russia and of a recombined LSDV as reported bySprygin et al (2018).…”
mentioning
confidence: 99%
“…LSD vaccination is conducted by those farmers that can access and/or afford the cost of vaccines and delivery of vaccines into the animals. This limitation poses a danger of misuse or abuse of the use of vaccines which may result in reversion of vaccine strains into virulent strains, consequently being responsible for new outbreaks [17]. This study therefore presents insights into the current viruses responsible for outbreaks in the country and compares them to viruses from neighboring countries and with LSDV vaccine strains.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination against LSD in Uganda is a responsibility of the livestock farmers rather than government. This may lead to misuse or abuse of vaccines bringing about co-infection and recombination of vaccine strains with virulent strains [17], resulting in virulent reversal of vaccine strains, which may lead to more outbreaks.…”
Section: Introductionmentioning
confidence: 99%